2017
DOI: 10.1016/j.geoderma.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Combined soil-terrain stratification for characterizing catchment-scale soil moisture variation

Abstract: 1Soil properties and terrain characteristics influence spatiotemporal patterns of soil 2 moisture across a watershed. To improve the predictive power of landscape hydrology models, it 3 is essential to consider both soil and terrain attributes when stratifying a catchment into similar 4 hydrologic functional units. In this study, we developed and validated a new catchment-scale 5 stratification scheme for the Shale Hills watershed by combining soil and terrain attributes in an 6 attempt to delineate soil-lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
20
2
Order By: Relevance
“…Differences in results across systems and measurement approaches suggest that assessment of which terrain metrics best represent individual hydrologic processes in various topographic and climatic environments should be explored further. For example, shallow soil moisture (10–40 cm) could be related to topographic wetness indices (UAA and TWI), whereas deeper soil moisture could be more related to elevation and vertical distance to stream, as was observed at Shale Hills (Baldwin et al, ). We suggest that the strong seasonality of catchment wetness at TCEF provides an ideal laboratory for examining when and to what degree individual topographic metrics might reflect hydrologic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in results across systems and measurement approaches suggest that assessment of which terrain metrics best represent individual hydrologic processes in various topographic and climatic environments should be explored further. For example, shallow soil moisture (10–40 cm) could be related to topographic wetness indices (UAA and TWI), whereas deeper soil moisture could be more related to elevation and vertical distance to stream, as was observed at Shale Hills (Baldwin et al, ). We suggest that the strong seasonality of catchment wetness at TCEF provides an ideal laboratory for examining when and to what degree individual topographic metrics might reflect hydrologic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small variation in vegetation distribution tested has negligible effects on the soil moisture pattern. Baldwin et al (submitted) calculated the temporal autocorrelation of soil moisture (2007–2010) from the 61 sites across Shale Hills. They found that the combination of topography and a digital soil map was significantly more accurate in characterizing watershed‐scale soil moisture variation than five other prevailing stratification systems, which indicates that the soil moisture pattern at the Shale Hills watershed is controlled by topography and soil types; our model results agree with their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Most locations estimate volumetric water content between 5‐ and 40‐cm depth, with valley floor and swale sites having extra measurements down to 1.3‐m depth (Lin et al, ). The soil moisture measurements at different depths are grouped into surface (top layer, usually represented by 5‐cm depth) and root zone (the average of all other layers) for simplicity (Baldwin et al, ). Here we used observed root zone soil moisture and observed 8‐cm soil temperature to drive the model.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in Shale Hills watershed have investigated hydrologic and biogeochemical processes in complex terrain. Shi et al (, ) and Baldwin et al () have shown predictable patterns of soil moisture, which are closely related to soil physical properties and topographic features. Weitzman and Kaye () calculated the N budget in the watershed and indicated that the watershed is N limited even given the relatively high N deposition that exists at present.…”
Section: Introductionmentioning
confidence: 98%